Impacts of priming on distinct immunosuppressive mechanisms of mesenchymal stromal cells under translationally relevant conditions - Nick Herger; Irina Heggli; Tamara Mengis; Jan Devan; Leonardo Arpesella; Florian Brunner; Oliver Distler; Stefan Dudli (Stem Cell Research & Therapy, 2024)
Abstract Background The multimodal properties of mesenchymal stromal cells (MSCs), particularly their ability to modulate immune responses is of high interest in translational research. Pro-inflammatory, hypoxic, and 3D culture priming are promising and often used strategies to improve the immunosuppressive potency of MSCs, but the underlying mechanisms are not well understood. Therefore, the aims of this study were (i) to compare the effects of pro-inflammatory, hypoxic, and 3D culture priming on the in vitro immunosuppressive potential of MSCs, (ii) to assess if immunosuppressive priming effects are temporally preserved under standard and translationally relevant culture conditions, and (iii) to investigate if the three priming strategies engage the same immunosuppressive mechanisms. Methods Functional in vitro T cell suppressive potency measurements were conducted to assess the impact of pro-inflammatory, hypoxic, and 3D culture priming on the immunosuppressive potential of human bone marrow-derived MSCs. Primed MSCs were either cultured under standard cell culture conditions or translationally relevant culture conditions, and their transcriptomic adaptations were monitored over time. Next-generation sequencing was performed to assess if different priming strategies activate distinct immunosuppressive mechanisms. Results (i) Pro-inflammatory, hypoxic, and 3D culture priming induced profound transcriptomic changes in MSCs resulting in a significantly enhanced T cell suppressive potential of pro-inflammatory and 3D culture primed MSCs. (ii) Priming effects rapidly faded under standard cell culture conditions but were partially preserved under translationally relevant conditions. Interestingly, continuous 3D culture priming of MSCs maintained the immunosuppressive potency of MSCs. (iii) Next-generation sequencing revealed that priming strategy-specific differentially expressed genes are involved in the T cell suppressive capacity of MSCs, indicating that different priming strategies engage distinct immunosuppressive mechanisms. Conclusion Priming can be a useful approach to improve the immunosuppressive potency of MSCs. However, future studies involving primed MSCs should carefully consider the significant impact of translationally relevant conditions on the preservation of priming effects. Continuous 3D culture could act as a functionalized formulation, supporting the administration of MSC spheroids for a sustainably improved immunosuppressive potency.